Assessment of smell dysfunction in mild symptomatic COVID-19 patients - Pradutdecha, Nannaphat; Bhakisongkhram, Gun; Paewponsong, Jirayupa (Disease Control Journal, 2024)
This quasi-experimental study examined smell function and was conducted at Suranaree University of Technology Hospital from April to July 2021. The study included 30 healthy participants in the control group and 125 admitted COVID-19 patients who had tested positive for SARS-CoV-2 using PCR. Subjectively, 49.6% of the COVID-19 patients reported smell loss. Olfactory assessment using phenyl ethyl alcohol (PEA) indicated smell dysfunction in 60.8% of the patients. Patients with COVID-19 were 6.2 times more likely to have smell dysfunction (95% CI 2.4-16.3). The mean duration of smell loss was 6.1 days (median 5 days, 95% CI 5.1-7.1 days, min-max: 1-21 days), which mostly followed other symptoms by 2.9 days (median 2 days, 95% CI 1.9-3.7 days, min–max: -2–13 days). The risk of smell dysfunction in COVID-19 patients were male (p=0.004) and smoking (p=0.04). No significant risk of smell dysfunction by age older than 45 years (p=0.528), BMI 25 more than kg/m2 (p=0.773) or severity of disease (pneumonia) (p=0.143) were observed.